Novel methodology for the selection and evaluation of R-strategies to support product design for circular economy - Schneider, Felix; Hansen, Sönke; Redeker, Julian; Klose, Glenn Inga; Rohwer, Viktoria; Strube, Martin; Mennenga, Mark; Vietor, Thomas; Völkerink, Oliver; Krinke, Stephan; et al. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
EU legislation demands manufactures to improve their product’s circularity. The 9R Framework organizes strategies of a circular economy in a hierarchical manner based on their respective effectiveness in promoting circularity. Manufacturers need to determine which of these strategies can be implemented for their products and how well a certain design meets the requirements of these strategies. Therefore, a methodology is proposed allowing to identify feasible R-strategies that are appropriate for a specific type of product. In the next step, the methodology evaluates how the unique characteristics of a particular component allow for the application of these strategies. This methodology is applied to a case study of a vehicle door, considering and comparing the circularity readiness of various design variants. A set of specific Circularity-indicators (C-indicators) for each strategy is used for this purpose. This methodology enables comparisons among different design options, highlighting their impact on the product and material recyclability. Ultimately, the methodology helps to identify challenges in a targeted manner that guide designers in creating products that effectively support beneficial R-strategies.